STUDY ON WORK - LIFE BALANCE AMONG THE EXECUTIVES IN IT INDUSTRY WITH SPECIAL REFERENCE TO TECHNOPARK, TRIVANDRUM, KERALA - K. S. CHANDRASEKAR; SUMA S.R; RENJINI S. NAIR AND ANU S.R (Asian Journal of Multidimensional Research, 2013)
IT industry in India has been a flourishing and dynamic one contributing significantly to the country’s GDP. IT organizations provide employment opportunities to immense talent pool and hence the role of work-life balance is coming into play. The industry is characterized by high attrition rate, low employee commitment level and stressful nature of job. This study emphasizes on the work-life balance of employees of IT organizations in Technopark, Trivandrum. The sample size taken is 350 employees and the procedure used was convenience sampling. The sample consists of 172males and133females IT employees. The major findings of the study were that there are some factors of work demand that interferes with the personal life which leads to an imbalance state, work-life balance is different based on gender and nature of jobs, work life balance has a positive relationship with job satisfaction etc. The study concluded that an efficient Work life Balance is detrimental to an employee for improving their job satisfaction and productivity. The company should focus on providing efficient Work Life Balance policies and programs to ensure proper Work Life Balance which will help them to improve the employee productivity and also to control the attrition rate. Above all the employees themselves should adopt certain precautionary methods for self management which should include a proper time utilization reducing burnout and stress